TOURISM ACTIVITIES AND IMPACT OF TOURISM ON ECONOMIC INFRASTRUCTURE (Conferencea, 2024)
After the independence of the Republic of Uzbekistan, fundamental reforms are being carried out in all sectors of the economy. In particular, the State attaches great importance to the development of tourism. The main infrastructures that make up the tourism sector are: accommodation facilities, catering services and transport services. Based on this, transport services play a key role in the development of the tourism sector. The development and improvement of transport services creates convenience for tourists and eases their travel. Through this, it is possible to achieve the development of tourism in the country.